PENGARUH BEBERAPA JENIS PAKAN TERHADAP PERKEMBANGAN ULAT HONGKONG (TENEBRIO MOLITOR.L.) (COLEOPTERA :TENEBRIONIDAE) (THE EFFECT OF SEVERAL TYPES OF FEED ON THE DEVELOPMENT OF HONGKONG CATERPILLARS (TENEBRIO MOLITOR) (COLEOPTERA: TENEBRIONIDAE)) - DARMIATI, NI NENGAH (AGRITROP; Vol. 29, No. 2 Juni 2010, 2012)
Purpose of this research is to determine the influence of several types of feed on the development of hongkong caterpillars (Tenebrio molitor) (Coleoptera: Tenebrionidae). Research conducted since September 2007 until July 2008 in the laboratory Plant Pests and Diseases Faculty of Agriculture, Udayana University. There are 11 types of feed tested, and each repeated 5 times, so there are 55 experimental units. The results show that the concentrate 521 gave the highest survival rate compared to other feed treatments, while the soybean feed gave lowest survival rates. Mixture concentrate 521 + banana peel is best feeding hongkong caterpillars, followed by the feed concentrate of 521, while cassava and soybean is less good feed.
Keywords: Tenebrio molitor , types of feed ,(Coleoptera: Tenebrionidae)